How Two English Primary Schools Promote Wellbeing - Jane Jones (Pedagogika)
This article is about how two English primary schools promote the wellbeing of primary-aged children and their teachers. No longer a privileged space for adults, wellbeing is increasingly a concern for children who, today, are subject to considerable stress. We currently inhabit a landscape of worry and pressure, often emanating from messages from news and social media that impact on children’s lives. Schools in the UK have excellent pastoral arrangements and have embraced the challenge of ensuring the wellbeing of their pupils and teachers as a fundamental right. The Personal, Social, Health, and Economic (PSHE) national arrangements for schools in England that I describe give details of the requirements for promoting the physical and mental wellbeing of pupils. Against this policy backdrop, I undertook to observe life in each of two schools and to interview their head teachers and the class teachers of 6-7-year-olds to understand how each school enacted wellbeing measures. The research question was simply “How do these schools understand and enact wellbeing for the children, and their teachers?” The schools were chosen as they were contextually very different but well-known in the community for the excellence of their pastoral and PSHE provision. I matched my data to the core theme of ‘Health and Wellbeing’ in the PSHE programme of study. The findings show how wellbeing is both readily identifiable as a “subject” in the primary curriculum and also embedded into the school culture and across the curriculum. The findings also emphasise the importance of the teacher as the one with daily contact and in prime position to observe and come to know and understand each child. The teachers emphasised the need to help children to build resilience and confidence to enable them to take advantage of opportunities and cope constructively with challenges in their exercise of life choices. I conclude that it is the whole school culture of wellbeing that foregrounds the conditions in which children can learn and develop their wellbeing in school and in the wider community.